2021
DOI: 10.1080/19490976.2021.1949097
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically synthesized exopolysaccharide of a probiotic strain Leuconostoc mesenteroides NTM048 shows adjuvant activity to promote IgA antibody responses

Abstract: Leuconostoc mesenteroides strain NTM048 produces an exopolysaccharide (EPS; glucose polymers 94% and fructose polymers 6%) with adjuvanticity for mucosal vaccination. Strain NTM048 includes three putative EPS-synthesizing genes, gtf1 and gtf2 for synthesizing glucose polymers, and lvnS for synthesizing fructose polymer. To elucidate the key polymer structure for adjuvanticity, two genes, gtf1 and gtf2, which were annotated as glycoside hydrolase family 70 enzyme genes, were expressed in Escherichia coli. Glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…6) NMR and GC-MS analyses of methylated derivatives of EPSs revealed that NTM048 EPS is a dextran consisting of an α-(1→ 6)-linked glucan with 4% α-(1→ 3) branches, and the remaining fructose polymer is composed of β-fructans. 7) Our group also found that enzymatically synthesized β-fructans exhibited lower IgA-inducing activity than NTM048 EPS, whereas α-glucans synthesized by a GH70 enzyme cloned from strain NTM048 possessed stronger IgA-inducing activity than NTM048 EPS. 8) These results indicate that α-glucans play an important role in the induction of IgA.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…6) NMR and GC-MS analyses of methylated derivatives of EPSs revealed that NTM048 EPS is a dextran consisting of an α-(1→ 6)-linked glucan with 4% α-(1→ 3) branches, and the remaining fructose polymer is composed of β-fructans. 7) Our group also found that enzymatically synthesized β-fructans exhibited lower IgA-inducing activity than NTM048 EPS, whereas α-glucans synthesized by a GH70 enzyme cloned from strain NTM048 possessed stronger IgA-inducing activity than NTM048 EPS. 8) These results indicate that α-glucans play an important role in the induction of IgA.…”
Section: Introductionmentioning
confidence: 63%
“…The characteristic peak at the branching point of the Glc(3,6-Glc) of fragment 3 (H-1 of branched-Glc: 5.32 ppm, J 1,2 = 4.0 Hz) was consistent with that of NTM048 EPS (H-1 of branched-Glc: 5.32 ppm, J 1,2 = 3.9 Hz). 7) With fragments 2 and 3 in hand, we next evaluated their IgA-inducing ability using murine Payer's patch cells. 8) In this assay, α-glucans synthesized by Gtf1 and Gtf2 were also used as controls in addition to NTM048 EPS.…”
Section: Resultsmentioning
confidence: 99%
“…20 ■ HOPS SYNTHESIS BY LAB HoPS consist of one monosaccharide�glucose or fructose� and are generally produced by the generas Weissella, Leuconostoc, Lactobacillus, and Pediococcus via the extracellular synthetic pathway. The process is mediated by specific glycosyltransferases (GTFs) and fructotransferases (FTFs) 21,22 and consists of two steps. In the first step, the sugar residues are cleaved into monomeric units and assembled into polymers with the aid of GTFs.…”
Section: ■ Eps Synthesis By Labmentioning
confidence: 99%
“…69 Whether it is a traditional probiotic or a new live biologic, mainstream clinical use has chosen to use probiotics after antibiotics, and there may be multiple reasons for such a combination order (Fig. 1): (1) the subsequent addition of probiotics can effectively occupy these ecological sites, thus competing to exclude the more resistant C. difficile strains, vegetative cells and spores; 9 (2) the addition of probiotics competes with the remaining C. difficile strains and their vegetative cells for nutrients essential for growth such as carbohydrates and amino acids, thus inhibiting the normal growth and metabolism of C. difficile; 19 (3) probiotics are able to secrete organic acids after colonization and affect the level of intestinal bile acid metabolism, especially enhancing the level of secondary bile acids, thus altering the intestinal growth environment to the detriment of C. difficile; 49,50 (4) after colonization, probiotics can secrete antimicrobial peptides, bacteriocins, extracellular polysaccharides and other types of antimicrobial substances, which have a direct killing effect on C. difficile strains; 64,[70][71][72] (5) probiotics can activate the intestinal immune system and enhance the related immune response to clear C. difficile; 73 and (6) probiotics can indirectly promote the growth of low-abundance beneficial microbes in the gut by "cross-feeding", thus co-antagonizing C. difficile. 74 Fig.…”
Section: Mode Of Action Of Probiotics In the Gutmentioning
confidence: 99%